Foundations of coding : compression, encryption, errorcorrection - Dumas, Jean-Guillaume.; Roch, Jean-Louis (Mathematician); Tannier, Eric.; Varrette, Sebastien (Hoboken, New Jersey : Wiley, 2015)
"This book offers a comprehensive introduction to the fundamental structures and applications of a wide range of contemporary coding operations. This text focuses on the ways to structure information so that its transmission will be in the safest, quickest, and most efficient and error-free manner possible. All coding operations are covered in a single framework, with initial chapters addressing early mathematical models and algorithmic developments which led to the structure of code. After discussing the general foundations of code, chapters proceed to cover individual topics such as notions of compression, cryptography, detection, and correction codes. Both classical coding theories and the most cutting-edge models are addressed, along with helpful exercises of varying complexities to enhance comprehension." --
3.5 Authentication, Integrity, Nonrepudiation, Signatures3.6 Key Management; Chapter 4: Error Detection and Correction; 4.1 Principle of Error Detection and Error Correction; 4.2 Error Detection by Parity-CRC Codes; 4.3 Distance of a Code; 4.4 Linear Codes and Cyclic Codes; 4.6 Convolutional Codes and Turbo Codes; Compression, Encryption, Correction: As a Conclusion; Problem Solutions; Solutions for Chapter 1; Solutions for Chapter 2; Solutions for Chapter 3; Solutions for Chapter 4; SOLUTION FOR THE "CASINO" EXERCISE; Bibliography; Index; End User License Agreement
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Coding theory; SCIENCE -- System Theory; TECHNOLOGY & ENGINEERING -- Operations Research; Coding theory; Electronic books; Electronic books